Callus Induction Of Phalaenopsis Stem (Phalaenopsis sp.) With NAA And TDZ Growth Regulatory In Vitro - Ni Wayan Deswiniyant; Ni Putu Gunami Mertaningsih; Ni Kadek Dwipayani Lestari (Fakultas Pertanian dan Bisnis Universitas Mahasaraswati Denpasar, 2025)
Orchid is an ornamental plant that is much favored by the wider community. Orchid flowers have a variety of interesting colors, shapes, and flower patterns. Cultivation is relatively long and requires special treatment. The purpose of this study was to determine the effectiveness of the explant sterilization method using fungicides and fungicides + HgCl2 to determine the response to explants by analyzing data using SPSS version.26 with ANOVA p-value <0.05, followed by Duncan's test to distinguish the average between treatments. o it requires propagation by tissue in vitro. The research design used in this study was RAL by tissue culture or in vitro using a flower stalk sample of the moon orchid (Phalaenopsis sp.) with K0 treatment, TN (TDZ 0.5 ppm, 1 ppm, 3 ppm + NAA 5 mg/L ) and T (TDZ 0,5 ppm, 1 ppm, 3 ppm) and with fungicide explant sterilization method 35 replicates and fungicide explant sterilization method + HgCl2 35 replicates. The results of tissue culture research on the response of explants with the fungicide sterilization method (p>0.05), while the results of the fungicide + HgCl2 response did not produce a bubble response because the explants were contaminated and browning. The results of the effectiveness of contamination in sterilization using fungicides (p<0.05), while fungicides + HgCl2 (p>0.05). The results of the effectiveness of browning on sterilization using fungicides and a combination of fungicides + HgCl2 (p>0.05)